Interactions of climate, socio-economics, and global mercury pollution in the North Water - Dietz, Rune; Mosbech, Anders; Flora, Janne; Eulaers, Igor (Ambio, 2018)
Despite the remoteness of the North Water, Northwest Greenland, the local Inughuit population is affected by global anthropogenic pollution and climate change. Using a cross-disciplinary approach combining Mercury (Hg) analysis, catch information, and historical and anthropological perspectives, this article elucidates how the traditional diet is compromised by Hg pollution originating from lower latitudes. In a new approach we here show how the Inughuits in Avanersuaq are subject to high Hg exposure from the hunted traditional food, consisting of mainly marine seabirds and mammals. Violation of the provisional tolerably yearly intake of Hg, on average by a factor of 11 (range 7–15) over the last 20 years as well as the provisional tolerably monthly intake by a factor of 6 (range 2–16), raises health concerns. The surplus of Selenium (Se) in wildlife tissues including narwhals showed Se:Hg molar ratios of 1.5, 2.3, and 16.7 in muscle, liver, and mattak, respectively, likely to provide some protection against the high Hg exposure.